Expression of Vimentin in Breast Carcinoma & its Correlation with Histopathological Parameters (Medical Forum Monthly, 2021)
Objective: To explore vimentin expression in different forms of breast cancer 2) to establish whether vimentin expression has a relationship to prognostic markers such as tumor size, grades, and status of the lymph node.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Pathology Hayatabad Medical Complex Peshawar from March 2019 to March 2020.Materials and Methods: 50 Specimens of radical modified mastectomy have been received by the Department of Pathology Hayatabad Medical Complex Peshawar. After history has been collected, specs of hematoxylin and eosin and immunehistochemically stained sections were checked and fixed to 10 percent forms of formalin.Results: In this research, the number of patients was 40-60 years of age. (It's about 51 years old on average.) In 23/50 (46%) of cases, Vimentin expression has been identified. It has demonstrated that its expression is highly linked to progressive malignancies (P-value 0,05) and that tumor cells transition from the epithelial to the mesenchymal. The bulk (48 percent) were classified as Invasive Carcinoma NST in Grade 2 and histopathologically identified. No link was found between the expression and status of the lymph node and the tumor size (P-value 0.05).Conclusion: Vimentin is more typically seen in advanced cancers. Its expression is unrelated to tumor size or nodal metastasis, implying that it may assist patients to obtain early treatment and live longer lives regardless of other prognostic variables.